The university, democracy and the public sphere - Holmwood, John (Taylor & Francis, 2016)
This article takes an historical approach to the rise and fall of the public university, relating its fate to specific developments in public policy. Particular attention will be paid to the United States and the United Kingdom since they are leading the drive the marketization of public higher education in the name of a neo-liberal global knowledge economy. It addresses how the functions of the university and its corporate form are being transformed and relates this to wider developments in the nature of the corporation and the relation between business and citizenship (or, market and democracy).